Therapeutic potential of luteolin in central precocious puberty: insights from a danazol-induced rat model - Zha, Zhijian; Lei, Enze; Wu, Xiaofan; Bai, Siyu; Huang, Tiantian; Lu, Tao; Wang, Zifeng; Cai, Yan; Li, Hui; Chen, Yao; Liu, Jianzhong (Frontiers in Endocrinology, 2025)
BackgroundRecently, central precocious puberty (CPP) is becoming a major public health concern worldwide due to its enhanced prevalence. Traditional Chinese medicine (TCM) compounds offer unique therapeutic advantages for treating this condition, and luteolin, a bioactive monomer compound commonly found in these herbs, has drawn increasing attention. However, the therapeutic effects of luteolin on CPP development remain unclear.MethodsA danazol-induced CPP model was established in Sprague-Dawley rats to explore the potential therapeutic effects of luteolin. Sexual development indicators, organ coefficients, gonadal histopathology, and sex hormone levels were evaluated to assess treatment outcomes. Additionally, a comprehensive approach involving network pharmacology, molecular docking, and transcriptomic analyses was used to identify luteolin-related signaling pathways and target proteins involved in CPP treatment. Finally, we carried out enzyme-linked immunosorbent assay (ELISA) and reverse transcription- quantitative polymerase chain reaction (RT-qPCR) for finding validation and exploring the underlying mechanisms.ResultsIn the danazol-induced CPP model, luteolin treatment significantly decreased the abundances of Estradiol (E2), luteinizing hormone serum, and follicle-stimulating hormone in sera; reduced organ coefficients and ovarian and uterine wet weights; and delayed vaginal opening. Network pharmacology and transcriptomic analyses revealed that luteolin exerted its therapeutic effects mainly by modulating immune and inflammatory pathways, including the tumor necrosis factor-α, Toll-like receptor, and IL-17 signaling pathways. Molecular docking demonstrated stable binding of luteolin to key targets such as Cxcl10, Cxcl11, Stat1, Tlr3, and Irf7. ELISA results confirmed that luteolin inhibited pro-inflammatory cytokines while promoting anti-inflammatory factors in the CPP model. Furthermore, RT-qPCR analysis revealed that luteolin enhanced Irf7 and Stat1 expression within the Toll-like receptor pathway, mainly by upregulating Tlr3, thereby enhancing the abundances of downstream effector molecules Cxcl10 and Cxcl11.ConclusionThis study is the first to determine that luteolin ameliorates CPP via the Toll-like receptor signaling pathway. These findings enhance our understanding of luteolin’s pharmacological actions and support its potential role in CPP treatment.